2021
DOI: 10.3390/cancers13122881
|View full text |Cite
|
Sign up to set email alerts
|

Male and Female Fertility: Prevention and Monitoring Hodgkin’ Lymphoma and Diffuse Large B-Cell Lymphoma Adult Survivors. A Systematic Review by the Fondazione Italiana Linfomi

Abstract: Background: Adult patients with Hodgkin lymphoma (HL) and diffuse large B-cell lymphoma (DLBCL) have prolonged survival but face the risk of treatment-induced impaired fertility. This systematic review, conducted by Fondazione Italiana Linfomi (FIL) researchers, aims to evaluate the incidence of treatment-related infertility, fertility preservation options, fertility assessment measures, and the optimal interval between the end of treatment and conception. Methods: MEDLINE, the Cochrane Library, and EMBASE wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 62 publications
(124 reference statements)
0
17
0
Order By: Relevance
“…Diffuse large B-cell lymphoma is the most frequent type among invasive lymphoma, representing 30.0-40.0% of all non-Hodgkin's lymphoma (NHL) (1,2). It is regarded as a heterogeneous lymphoma in clinical features, tumor biology, and prognosis (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Diffuse large B-cell lymphoma is the most frequent type among invasive lymphoma, representing 30.0-40.0% of all non-Hodgkin's lymphoma (NHL) (1,2). It is regarded as a heterogeneous lymphoma in clinical features, tumor biology, and prognosis (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…The EB protocol, comprising two gonadotoxic alkylating agents, cyclophosphamide and procarbazine, is applied in the management of HL and is associated with higher PFS than ABVD. However, this often comes at the expense of increased treatment-related gonadotoxicity [47,48] that is an established contributing factor to reduced BMD. As early as 4 decades ago, Waxman et al revealed long-term gonadotoxicity of the MOPP (nitrogen mustard, vinblastine, prednisolone, procarbazine) regimen in patients with advanced-stage HL [31].…”
Section: Discussionmentioning
confidence: 99%
“…Infertility and pregnancy loss is a well-recognized phenomenon in other blood disorders affecting B lymphocytes, such as lymphoproliferative diseases (ie, Hodgkin lymphoma and B NHLs). Infertility in these cases, which is due to both the disease (ie, azoospermia in males, reduced ovarian reserve, premature menopause in females) and the anticancer treatment, is reversible in most cases [ 17 ].…”
Section: Discussionmentioning
confidence: 99%